Comparative analysis of the transportation of select petrochemicals. (1st January 2013) - Stamber, Kevin L.; Ehlen, Mark A.; Pepple, Mark; Welk, Margaret E.; Deng, Haoran; Lewis, Carol A.; Clark, Latissha; Bryant, James R.; Jasek, Debbie
Large volumes of hazardous cargo move across US roadways daily. Field counts are conducted on sections of roadway that provide aggregated volumes. A high level of interest exists in acquiring the capability to replicate these periodic field counts through a computer-simulated programme. Base data and computer simulation models were identified, which could be coordinated with field counts. The corridor traversing the core of Houston's petrochemical industry served as the study area. Simulation data on producers and chemicals within the area were analysed, and alternate means of transportation were identified, to select chemicals most likely to be transported to the geographic area by truck. The likely frequency of shipments was calculated and compared to the field data. The study outcome reflected a good fit between the simulation and the field counts, providing positive conditions for application of the model to other corridors and showing strong potential for its predictive value.